Strengthening Digital Marketing Capacity through SEO Strategies for MSMEs in Cianjur Regency - Syafei, M Yani; Wahdiniwaty, Rahma Wahdiniwaty; Novianti, Windi; Iffan, Muhammad (EQUATOR SINAR AKADEMIA, 2025)
A strategic approach to meet the issues given by the rapid growth of online markets is the improvement of digital marketing capability among Micro, Small, and Medium Enterprises (MSMEs) in Gekbrong District, Cianjur Regency, through Search Engine Optimisation (SEO) methods. By enhancing their understanding and practical skills in the use of SEO strategies, including keyword research, on-page optimisation, creating excellent content, and efficiently utilising Google My Business, this community engagement program aims to empower nearby MSMEs. The training approach, which involved MSME players from a variety of business sectors like agribusiness, handicrafts, and culinary arts, blended theoretical lessons, practical experience, and mentoring. The findings showed that organic traffic increased on average. Participants also mentioned increased internet sales and market expansion outside of Cianjur. The primary obstacles were corporate actors' poor technological knowledge and the lack of adequate digital infrastructure. As a result, the program suggests creating SEO learning groups, creating training materials in regional languages, and offering more reliable internet connection. The application of SEO tactics has been successful in improving MSMEs' digital marketing capabilities in Gekbrong District, and it may be replicated in other areas to promote digital economic inclusion at the community level.